PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA TRANSPORTASI OJEK ONLINE (Studi Pada Pelanggan GrabBike Di Kota Medan). - Sianipar, Gloria J.M (UNIKA Santo Thomas, 2019)
This research aims to analyze the impact of Service Quality, Price Perception and Brand Image on Customer Satisfaction of The User of Online Transportation (Case on The User of GrabBike in Medan). Data collection empasys a sample of 100 from 32 items using Likert Scale standard of measurement. In this research, free variables consist of service quality, price perception, and brand image. Bound variable is customer satisfaction. Testing includes test the validity, reliability test and assumptions classic. While the method of data analysis used multiple linear regression.The result of ttest showed that the service quality, price perception and brand image has a significant effect on customer satisfaction. The results of signification value for each variable, both variables X and variable Y is above the alpha value (0.05), resulting in acceptance of H1and H0rejection. The result of F test showed that the service quality, price perception and brand imageworked togetherto gave positive and significant contribute on customer satisfaction.In accordance with a multiple linear regression equation, Y = 2,689 + 0,106 X1 + 0,133X2 + 0,141X3 +e. So in essence, variable X has a significant effect at customer satisfaction.The result of this research were brand image has the highest significant effect to customer satisfaction.